Phase transitions and critical phenomena: universality and non-universal features - Ilnytskyi, J.; Holovatch, Y.; Kozitsky, Y. (Condensed Matter Physics, 2013)
This special issue of the CMP is devoted to phase transitions and critical phenomena. Several recent decades of intensive, sometimes even frantic, and fruitful activities might produce an impression that all principal work in this field has already been completed and nothing really new can be found. Of course, this is far from being true, and the aim of the present issue is to give an evidence that the field is still fertile and thankful to those who work hard on it. We hope that the readers will find this evidence in the presented papers for which we cordially thank their authors who share this aim of ours and our devotion to the subject.